Are specific skills an obstacle to labor market adjustment? - Lamo, Ana [Verfasser]; Messina, Julian [Verfasser]; Wasmer, Etienne [Verfasser] (My University, 2011)
"This paper shows that specialized education reduces workers' mobility and hence their ability to cope with economic changes. We illustrate this point using labor force data from two countries having experienced important macroeconomic turbulence; a large economy with rigid labor markets, Poland, and a small open economy with increased flexibility, Estonia. We find that holding a vocational degree is associated with much longer unemployment duration spells and higher likelihood of leaving activity for older workers. We then build a theoretical framework in which young agents' careers are heavily determined by the type of initial education, and analyze the transition to a new steady-state after a sectoral demand shift. Quantitative exercises suggest that the over-specialization of the labor force in Poland led to much higher and persistent unemployment compared to Estonia during the period of EU enlargement. Traditional labor market institutions (wage rigidity and employment protection) lead to an increase of the unemployment gap, but to a lesser extent." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; G 1.3.1 Bildungsangebot & -nachfrage; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.3.3.3 Mobilität; I 2.2.2 Osteuropa; Fachwissen; Spezialisierung; Bildungsabschluss; Berufseinmündung; Zweite Schwelle; Arbeitslosigkeit; Berufliche Mobilität; Empirische Untersuchung; Polen; Estland